Isosteric phosphonate pyrrolidine-based dinucleoside monophosphate analogues - Vanek, Václav; Budesínský, Milos; Kavenová, Ivana; Rinnová, Markéta; Rosenberg, Ivan (Nucleosides, nucleotides & nucleic acids, 2003)
A novel alpha- and beta-configured pyrrolidine nucleoside phosphonates in adenine series were synthesized from trans-4-hydroxy-L-proline as starting material. d(ApA) analogues were also prepared and studied with respect to their hybridization properties with polyU.
Keywords: Adenosine; Poly U; Oligonucleotides; hydroxyprolin; oligonukleotidy; vazebná místa; nukleotidy; pyrrolidiny; indikátory a reagencie; Dinucleoside Phosphates; adenosin; Pyrrolidines; Stereoisomerism; stereoizomerie; Indicators and Reagents; Nucleotides; organofosfonáty; Hydroxyproline; poly U; Organophosphonates; dinukleosidfosfáty; Binding Sites